GOALS AND TASKS OF ENSURING WOMEN'S EMPLOYMENT IN THE SOCIAL PROTECTION SYSTEM AND IMPLEMENTATION (Scientific journal of the Fergana State University, 2024)
This article analyzes the complex issues related to the establishment of a democratic state and an independent economy in thesociety of Uzbekistan, the elimination of the consequences of the planned administrative system, and the need to transition to market relations.It is also included in the income tax levied on the wages of employees of a class in need of social protection (disabled persons) and certaincategories (single mothers with minor children). Ensuring women's employment did not fail to have an impact on the rapid development of theeconomy. This will also increase the gross domestic product of the country.